2017
DOI: 10.7189/jogh.07.020410
|View full text |Cite
|
Sign up to set email alerts
|

The cost of diabetes in Latin America and the Caribbean in 2015: Evidence for decision and policy makers

Abstract: BACKGROUNDThe financial implications of the increase in the prevalence of diabetes in middle–income countries represents one of the main challenges to health system financing and to the society as a whole. The objective of this study was to estimate the economic cost of diabetes in Latin America and the Caribbean (LAC) in 2015.METHODSThe study used a prevalence–based approach to estimate the direct and indirect costs related to diabetes in 29 LAC countries in 2015. Direct costs included health care expenditure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 13 publications
1
56
1
8
Order By: Relevance
“…Barcelo et al [4] found that, most of the direct costs of treating DM in Latin America are related to the treatment of complications. The cost of a patient without chronic complications with HbA1c > 10% is 2.4 times higher than that of a patient better controlled with HbA1c < 8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barcelo et al [4] found that, most of the direct costs of treating DM in Latin America are related to the treatment of complications. The cost of a patient without chronic complications with HbA1c > 10% is 2.4 times higher than that of a patient better controlled with HbA1c < 8%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the high disease burden, DM has a high economic impact deriving from direct and indirect costs, with an annual estimated total cost of US $ 102 to 123 billion, including parameters such as premature mortality and temporary or permanent disability [1,2,4]. In Latin America, about 25% of health expenditures refer to the treatment of DM and its complications [4]. Brazil is one of the top 10 countries with the highest number of people with DM in the world and currently is the 5th in the ranking [5].…”
Section: Introductionmentioning
confidence: 99%
“…Os custos diretos incluíram medicamentos, hospitalizações, consultas e tratamento de complicações que totalizaram U$24,6 bilhões e os custos indiretos, que se referem à perda de renda por incapacidade permanente ou temporária e morte prematura, totalizando U$19 bilhões. Dentre os 25 países incluídos nesta análise, o Brasil é o que tem os maiores custos relacionados à doença (2) . É importante ressaltar o ônus financeiro substancial que o diabetes impõe à sociedade, além dos custos que não podem ser mensurados, como dor e sofrimento, recursos dos cuidados prestados por cuidadores não remunerados e custos associados ao diabetes não diagnosticado (3) .…”
Section: Introductionunclassified
“…In addition to increasing average annual costs for the management of diabetes and its complications, there are epidemiological changes associated with the increasing trend of the prevalence of diabetes and its complications in recent and future years. In economic terms, the epidemiological burden observed and expected for these countries represents a high financial burden for health systems, patients, families, and society as a whole …”
mentioning
confidence: 99%
“…Unlike other diseases, in the case of diabetes the economic and social effects are associated not only with the direct costs of annual case management and the main complications of diabetes (nephropathy, retinopathy, peripheral vascular disease, cardiovascular disease, and neuropathy), but also, more importantly, with the indirect costs of premature mortality, temporary disability, and permanent disability attributable to diabetes …”
mentioning
confidence: 99%